Efektivitas Senam Anemiaction Terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri - Meda Yuliani; Tika Lubis; Lia Novita (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Anemia remains a significant global public health issue affecting adolescent girls and contributing to reduced physical endurance, lowered cognitive focus, and long‑term reproductive risks. This study aims to evaluate the effectiveness of Anemiaction exercise as a low‑intensity aerobic activity designed to stimulate erythropoietin and improve hemoglobin levels. Using a one‑group pretest–posttest design involving 30 adolescent girls, hemoglobin levels were measured before and after four weeks of exercise performed three times weekly. Results showed an increase from 11.2 g/dL to 12.1 g/dL, indicating significant improvement. Anemiaction exercise can serve as an effective, non‑pharmacological school‑based intervention for anemia prevention. Keywords: Hemoglobin, Anemiaction Exercise, Anemia, Adolescent Girls.  ABSTRAK Anemia merupakan masalah kesehatan global yang banyak dialami remaja putri dan berdampak pada penurunan konsentrasi belajar, daya tahan tubuh, serta risiko kesehatan reproduksi jangka panjang. Penelitian ini bertujuan menilai efektivitas senam Anemiaction sebagai aktivitas aerobik intensitas ringan yang dapat merangsang eritropoietin dan meningkatkan kadar hemoglobin. Desain penelitian menggunakan one‑group pretest–posttest dengan 30 remaja putri. Kadar hemoglobin diukur sebelum dan sesudah intervensi selama empat minggu. Hasil menunjukkan peningkatan dari 11,2 g/dL menjadi 12,1 g/dL. Senam Anemiaction efektif sebagai intervensi non‑farmakologis untuk pencegahan anemia berbasis sekolah Kata Kunci: Hemoglobin, Senam Anemiaction, Anemia, Remaja Putri.